The modulatory effect and the mechanism of flavonoids on obesity. Issue 8 (18th June 2019) - Song, Dan; Cheng, Lu; Zhang, Xin; Wu, Zufang; Zheng, Xiaojie
Abstract: With the improvement of living standards, obesity has become a serious health problem all over the word. Currently, the methods and drugs for obesity treatment have some limitations and side effects. Flavonoids are active constituents with various biological activities, widely found in plants, and numerous studies have shown that flavonoids can inhibit obesity and related metabolism disorders effectively. This perspective reviews the recent progress in understanding the anti‐obesity effects of flavonoids through modulating food intake, enzyme activities, nutrition absorption, adipogenesis and adipocyte lifecycle, thermogenesis, energy consumption, and intestinal microbiota. Practical applications: Natural bioactive substance flavonoids have anti‐obesity property, which may play a role in anti‐obesity drugs or functional food without any side effects. Flavonoids can inhibit weight gain directly or through their biologically active metabolites by various potential pathways. A better understanding of the modulatory effect and the mechanism of flavonoids on obesity will allow us to better utilize flavonoids in plants to treat obesity and related metabolic syndrome.